Performance of Combined Electrocoagulation-Advanced Electrochemical Oxidation Used for Oil Field Produced Water Treatment - Al-Khafaji, Rand Q. kadhem; Mohammed, Abdul Halim A-K (Journal of Petroleum Research and Studies, 2021)
Considerable amounts of produced water (PW) are usually accompanied with the production of oil. This study proposed a combination of electrocoagulation (EC) - electro- Fenton (EF) process for oxidation organic compounds in PW to reduce the chemical oxygen demand (COD) to below regulation limits. The PW used in this study was collected from oilfield in the Midland Oil Company. Pretreatment of the PW was conducted using batch EC technique with aluminum electrodes to eliminate the suspended and dissolved solids and to reduce the COD and treatment cost. Optimization of EC process revealed that optimum current density, pH, and reaction time were 7.83 mA/cm2, 7.24, 20.40 minutes respectively. Under these conditions the COD removal percentage was 73.97% starting from initial COD of 1730 mg/l.Batch and continuous electro-Fenton processes were investigated using dimensionally stable anode Ti-RuO2/IrO2 and activated carbon fiber felt (ACFF) cathode. The effect of crucial process variables on COD removal efficiency was investigated using response surface methodology. A second order polynomial model equations were constructed and the results was analyzed by the analysis of variance (ANOVA). It was concluded that a combination of electrocoagulation followed by electro-Fenton process is effective for treating oilfield produced water and further improvement can be achieved by photo assisting the process. A total COR removal efficiency of 98% was achieved.